Development LINE Bot for Tourism Promotion in Tak Province - Joobanjong, Wanchana; Muntaworn, Panupong; Mekurai, Chayuti; Sinpromma, Tanin; Suesatsakulchai, Apichai (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2025)
The research began with data collection on tourism in Tak and interviews with experts to gather requirements for the LINE bot’s functionality. Information from these expert interviews was used to define the functionality of the LINE bot. The design and development process involved creating graphics for display and menu interactions within the LINE application. The tourism data was designed and stored in MySQL. A web application was developed using HTML, CSS, JavaScript, and PHP to manage and present Tak’s tourist data via the LINE platform. Messaging API and LIFF were used for interaction between the user and the LINE bot. An evaluation of tourist satisfaction with the LINE bot was conducted, revealing a high level of user satisfaction.